Genetic interaction with temperature is an important determinant of nematode longevity. Issue 6 (21st September 2017) - Miller, Hillary; Fletcher, Marissa; Primitivo, Melissa; Leonard, Alison; Sutphin, George L.; Rintala, Nicholas; Kaeberlein, Matt; Leiser, Scott F.
Summary: As in other poikilotherms, longevity in C. elegans varies inversely with temperature; worms are longer‐lived at lower temperatures. While this observation may seem intuitive based on thermodynamics, the molecular and genetic basis for this phenomenon is not well understood. Several recent reports have argued that lifespan changes across temperatures are genetically controlled by temperature‐specific gene regulation. Here, we provide data that both corroborate those studies and suggest that temperature‐specific longevity is more the rule than the exception. By measuring the lifespans of worms with single modifications reported to be important for longevity at 15, 20, or 25 °C, we find that the effect of each modification on lifespan is highly dependent on temperature. Our results suggest that genetics play a major role in temperature‐associated longevity and are consistent with the hypothesis that while aging in C. elegans is slowed by decreasing temperature, the major cause(s) of death may also be modified, leading to different genes and pathways becoming more or less important at different temperatures. These differential mechanisms of age‐related death are not unlike what is observed in humans, where environmental conditions lead to development of different diseases of aging.